2020
DOI: 10.1108/ijpdlm-05-2019-0134
|View full text |Cite
|
Sign up to set email alerts
|

Motor carrier spot market: trust-building in public e-marketplaces

Abstract: PurposeThis research aims at understanding the routes public e-marketplaces take, in the motor carrier spot market, to generate trust among participants.Design/methodology/approachThis work borrows cue signaling theory and an e-marketplace content analysis instrument from information systems literature. Our primary data captures differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 74 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…A few studies related to carrier behaviors consider the design of the spot marketplace. For example, studies have demonstrated support for centralized market mechanisms (Figliozzi, 2006; Figliozzi et al, 2003; Haughton et al, 2022), cue signaling to instill trust between parties (Collignon et al, 2020), and matching to optimize for backhauls (Muckell et al, 2009) to eliminate inefficiencies.…”
Section: Summary Of the Existing Literaturementioning
confidence: 99%
“…A few studies related to carrier behaviors consider the design of the spot marketplace. For example, studies have demonstrated support for centralized market mechanisms (Figliozzi, 2006; Figliozzi et al, 2003; Haughton et al, 2022), cue signaling to instill trust between parties (Collignon et al, 2020), and matching to optimize for backhauls (Muckell et al, 2009) to eliminate inefficiencies.…”
Section: Summary Of the Existing Literaturementioning
confidence: 99%
“…Theoretical foundation: signaling theory Signaling theory has gained attention in the emerging consumer-centric supply chain management literature (e.g., Hossain et al, 2018;Peinkofer and Jin, 2023) and has been applied in various contexts such as supplier monitoring activities (Duan et al, 2021), supply chain transparency (Mollenkopf et al, 2022), motor carrier spot market (Collignon et al, 2020), and retailer service recovery (Jin et al, 2023). Signaling theory explains the decision-making process of a signaler and receiver while managing information asymmetry (Spence, 1973(Spence, , 2002.…”
Section: Ijpdlm 539mentioning
confidence: 99%
“…, 2021), supply chain transparency (Mollenkopf et al. , 2022), motor carrier spot market (Collignon et al. , 2020), and retailer service recovery (Jin et al.…”
Section: Introductionmentioning
confidence: 99%